Multifunctional Intelligent Invisible Bookcase Bed Based on Voice Control - Wen Xinhao; Ma Qihua; Zhang Xurui; Xu Shicheng (IJRDO -Journal of Computer Science Engineering, 2020)
Aiming at the single intelligent and multifunctional furniture on the market, a multifunctional intelligent invisible bookcase bed based on voice control is proposed. This article has designed the structure of the bookcase bed in detail; introduced the principles of hardware control and software control. Experiments show that the bookcase bed in this book can complete the expected functions, and through voice control to achieve the intelligent control of the bookcase bed.